Toksisitas Metoksifenozida terhadap Helicoverpa Armigera = Toxicity of Methoxyfenozide to Helicoverpa armigera M. - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2003)
Ecdysone agonists were a new group of insecticides with unique mode of action. They mimiced the natural moulting hormone 20-hydroxyecdysone. The objective of this study was to determine the toxicity of the ecdysone agonist methoxyfenozide to Helicoverpa armigera (Lepidoptera: Noctuidae) compared to other novel insecticides Cryl Ac, and p-cyflutrin currently used to control this insect. The bioassays were carried out by exposing newly hatched larvae of H. armigera to artificial diets dipped in solutions of methoxyfenozide, CrylAc or (3-siflutrin. Larvae were exposed for five days and mortality was recorded every 24 hours. Based on the LC^ and LC,,, values, the toxicity of methoxyfenozide toH. armigera was found to be lower than CrylAc and P-cyflutrin.